The good, the bad, and the ugly: a pragmatic approach for revisiting ethics and internet politics - Saldías, Osvaldo; Züger, Theresa C. (Acta Bioethica, 2013)
The article stems from a broader ongoing research project on Internet, Global Constitutionalism and Ethics. We attempt to brisk up traditional ethical thinking against the background of urgent questions concerning the Internet. By revisiting the perspective of cosmopolitanism that was inspired by Kant's thesis of a universal rationality, reflecting upon Hanna Arendt's critical analysis of moral claims and political outcome, and building on Capurro's "net ethics", we introduce a perspective aiming at an intercultural understanding that might guide our actions in global politics in times of the so called digital era. The article advances the idea by Hannah Arendt that a concrete example as such has moral relevance and therefore makes a case to foster this approach using "best practices" as explicit examples to follow.